Anticonvulsant action of GABA-B receptor agonist SKF97541 differs from that of baclofen - Mares, P (Physiological research, 2008)
GABA-B receptor agonist SKF97541 exhibits age-dependent anticonvulsant and proconvulsant actions in developing rats. It suppressed tonic phase of generalized seizures induced by pentetrazol in 7-, 12- and 18-day-old rats and increased their latency in 7- and 12-day-old animals. Other results in 18-day-old animals are not so clear. SKF97541 blocked the appearance of minimal clonic seizures, but tended to decrease latencies of both types of seizures. In addition, it significantly decreases latency of generalized seizures in adult rats. The mixed effects of SKF97541 are in agreement with those of baclofen but there are substantial differences between the actions of these two agonists in individual age groups.
Keywords: Anticonvulsants; Pentylenetetrazole; Seizures; receptory GABA-B; antikonvulziva; Receptors, GABA-B; organofosforové sloučeniny; Dose-Response Relationship, Drug; Baclofen; záchvaty; věkové faktory; krysa rodu Rattus; zvířata; GABA agonisté; pentylentetrazol; potkani Wistar; agonisté receptorů GABA-B; Rats, Wistar; Reaction Time; Male; Organophosphorus Compounds; reakční čas; Rats; GABA Agonists; vztah mezi dávkou a účinkem léčiva; GABA-B Receptor Agonists; Age Factors; baklofen; Animals; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech